2019
DOI: 10.1038/s41388-019-0813-7
|View full text |Cite
|
Sign up to set email alerts
|

Addiction to DUSP1 protects JAK2V617F-driven polycythemia vera progenitors against inflammatory stress and DNA damage, allowing chronic proliferation

Abstract: Inflammatory and oncogenic signaling converge in disease evolution of BCR-ABL-negative myeloproliferative neoplasms, clonal hematopoietic stem cell disorders characterized by gain-of-function mutation in JAK2 kinase (JAK2V617F), with highest prevalence in patients with polycythemia vera (PV). Despite the high risk, DNA-damaging inflammatory microenvironment, PV progenitors tend to preserve their genomic stability over decades until their progression to post-PV myelofibrosis/acute myeloid leukemia. Using induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 82 publications
1
42
0
Order By: Relevance
“…In addition, the aforementioned extent of Chk2 activation in CML (high) and PV (low) likely reflects subcellular localization of P-ATM [90,91]. Our further (published in [82]) IHC staining of patients' bone marrow sections from PV revealed low nuclear staining for activated ATR (P-ATR at T1989), and barely detectable expression of a marker for oxidative DNA lesions 8-oxoguanine (8-oxoG), as well as very low staining for a marker of global nuclear DDR activation, Ser 139-phosphorylated histone H2AX (γH2AX) [82]. These data suggested that despite inflammatory microenvironment and JAK2 V617F oncogene-driven myeloproliferation, certain mechanisms must mitigate the potential genotoxic impact of the overall oncogenic program controlled by JAK2 V617F, thereby allowing for PV chronic proliferation with relatively stable genome.…”
Section: Role Of Ddr In Polycythemia Veramentioning
confidence: 60%
See 4 more Smart Citations
“…In addition, the aforementioned extent of Chk2 activation in CML (high) and PV (low) likely reflects subcellular localization of P-ATM [90,91]. Our further (published in [82]) IHC staining of patients' bone marrow sections from PV revealed low nuclear staining for activated ATR (P-ATR at T1989), and barely detectable expression of a marker for oxidative DNA lesions 8-oxoguanine (8-oxoG), as well as very low staining for a marker of global nuclear DDR activation, Ser 139-phosphorylated histone H2AX (γH2AX) [82]. These data suggested that despite inflammatory microenvironment and JAK2 V617F oncogene-driven myeloproliferation, certain mechanisms must mitigate the potential genotoxic impact of the overall oncogenic program controlled by JAK2 V617F, thereby allowing for PV chronic proliferation with relatively stable genome.…”
Section: Role Of Ddr In Polycythemia Veramentioning
confidence: 60%
“…Our own early (unpublished) analysis depicted in Figure 1b revealed differences between Chk2 activation in CML and PV, suggesting differences in functions of its upstream regulator ATM kinase. Although the activated, auto-phosphorylated form of ATM (P-ATM) localizes to the nucleus in bone marrow progenitors of myeloid malignancies including MDS [87,88] and CML ( [45] and Figure 2a), our immunohistochemistry (IHC) staining against P-ATM at S1981 revealed predominantly cytoplasmic P-ATM immunoreactivity in PV progenitors and distinct nuclear staining (and lack of cytoplasmic staining) only in post-PV MF ( [82] and Figure 2b). These data indicate that although ATM in CML (and MDS and post-PV MF) progenitors regulate its downstream substrates and cell cycle checkpoints mainly from the nucleus, this is different in PV progenitors, where ATM exerts its actions mainly from the cytoplasm.…”
Section: Role Of Ddr In Polycythemia Veramentioning
confidence: 93%
See 3 more Smart Citations